Institute of Constitutional Responsibility in the Republic of Armenia - Hakobyan, R. (Bulletin of Yerevan University C: Jurisprudence, 2020)
The article is dedicated to the institute of constitutional responsibility. It is stated that in the state legal system of Armenia, constitutional responsibility should be perceived within the following perspectives: as an independent type of legal responsibility; a special constitutional legal institution; a constituent part of the constitutional legal status of public authorities; as well as a part of the Republic of Armenia`s constitutional security system.It is noted that the institute of constitutional responsibility in the Republic of Armenia should receive not only a "right to life" but also a "right to citizenship".